A Two-Stage Framework for Object Detection in Low-Light Images Using Image Enhancement and Deep Learning Models - Asmaa Sabea (Indonesian Journal Publisher, 2026)
In low-lighting scenarios in object detection, a major challenge exists owing to reduced lighting, greater noise, lower contrast, and lighting changes. Thus, such scenarios have a significant effect on vision-based systems used in surveillance, path detection for autonomous vehicles, and security surveillance. A two-tier method using classical image processing and a deep learning platform for object detection in images is proposed and implemented in this work. The first stage uses a dedicated image processing chain aimed at increasing image brightness, contrast, and clarity while eliminating image noise. These processed images are then subjected to evaluation by two separate object detection models: YOLOv9 and Faster R-CNN. From ExDark dataset testing, the effectiveness of the method implemented has a mean Average Precision value of 96% at IOU= 0.50 for YOLOv9 and 88% mAP@50 for Faster R-CNN.